2022
DOI: 10.1021/acs.jpclett.2c00259
|View full text |Cite
|
Sign up to set email alerts
|

Watching Excited-State Symmetry Breaking in Multibranched Push–Pull Molecules

Abstract: The emissive properties of symmetric molecules containing several donor− acceptor branches are often similar to those of the single-branched analogues. This is due to the at least partial localization of the excitation on one branch. Detailed understanding of this excited-state symmetry breaking (ES-SB) requires the ability to monitor this process in real time. Over the past few years, several spectroscopic approaches were shown to enable visualization of ES-SB and of its dynamics. They include the detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…That is, the sequential CS and CR processes from the partial CT state dominate the excited state deactivation and are responsible for fluorescence quenching in the studied DA and DAD fluorescence system. These results further elucidate that the ESSB behaviors of the current DAD system lead to the identical excited state dynamics to that of the control DA system. , That is, the photoexcited LE species could undergo the ESSB process, degenerates to the one side of the DAD skeleton, and forms the partial CT state, SB-CT, that is mainly distributed on the acceptor and one of donor arms as reflected in the simple DA molecule (Scheme ). Then either the formed partial CT state deactivates via the radiative transition channel (strong PL) in low-polar solvent or rapid CS and CR processes further occur, recovering to the ground state in polar solvent.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…That is, the sequential CS and CR processes from the partial CT state dominate the excited state deactivation and are responsible for fluorescence quenching in the studied DA and DAD fluorescence system. These results further elucidate that the ESSB behaviors of the current DAD system lead to the identical excited state dynamics to that of the control DA system. , That is, the photoexcited LE species could undergo the ESSB process, degenerates to the one side of the DAD skeleton, and forms the partial CT state, SB-CT, that is mainly distributed on the acceptor and one of donor arms as reflected in the simple DA molecule (Scheme ). Then either the formed partial CT state deactivates via the radiative transition channel (strong PL) in low-polar solvent or rapid CS and CR processes further occur, recovering to the ground state in polar solvent.…”
mentioning
confidence: 54%
“…Wang et al and other research groups successively reported the efficient near-infrared delayed fluorescence OLEDs using a DAD-type charge-transfer (CT) compound. Meanwhile, several corresponding donor–acceptor (DA)-type fluorescence chromophores have also been reported with comparable device performances. However, systematic studies are rarely reported on the differences of electronic and photophysical properties between DAD and DA-type fluorescence chromophores. In previous studies, symmetric quadrupolar DAD/ADA molecules that contain two or more electron donors or acceptor branches could undergo excited-state symmetry breaking (ESSB), that is, a transition from the symmetric multipolar to asymmetric dipolar states, and then exhibited the similar CT dynamics with single-branched DA analogue, such as solvatochromism. Herein we addressed this issue via a comparative study on the excited state dynamics of DA and DAD fluorescence systems (Figure ) in combination of theoretical calculations and transient absorption (TA) spectroscopy. Results show that DA and DAD molecular systems exhibit an almost identical excited state dynamics including similar fluorescence emission behaviors, which are attributed to the distinctive ESSB phenomenon observed in the DAD system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Differently, in the case of the quadrupolar molecule, emission maxima very close to those revealed for the dipolar Py-1 were found. This behavior might suggest the possibility of excited state symmetry breaking for the quadrupolar system in polar media, leading to localization of the excitation on a single branch of the molecular structure . Indeed, the emission spectra of the dipolar and quadrupolar systems were found to be quite similar in CHCl 3 (λ max,em = 485 nm for Py-1 and λ max,em = 472 nm for Py-3 ) and even more similar in the more-polar DMSO (λ max,em = 522 nm for Py-1 and λ max,em = 516 nm for Py-3 ).…”
Section: Resultsmentioning
confidence: 95%
“…25 In multibranched molecules having formally equivalent branches, symmetry breaking implies a geometrical distortion leading to inequivalent branches in the excited states, as recognized and thoroughly investigated, from both experimental and theoretical perspectives. [26][27][28][29][30][31][32][33][34][35] Symmetry breaking also plays a crucial role in the generation of charge separation in multichromophoric assemblies. [36][37][38][39][40][41][42] In multibranched multipolar chromophores, whose low-lying excitations are dominated by charge transfer degrees of freedom, symmetry breaking is driven by polar solvation, as theoretically predicted 21,26 and experimentally veried.…”
Section: Introductionmentioning
confidence: 99%